An Ontology of Implementation Plans of Historic Centers: A Case Study Concerning Sardinia, Italy - Lai, Sabrina; Zoppi, Corrado (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper discusses some key points related to the ontology of implementation plans of historic centers (IPHCs). We study this ontology by discussing its implementation in the context of the provisions of the Sardinian Regional Landscape Plan (RLP), and put in evidence some important general observations, coming from the case study, concerning the utility and effectiveness of the ontological conceptual framework in order to help planners and decision makers understand and structure the assessment process of implementation plans.